A radar-like DNA monitor for RNase H-targeted natural compounds screening and RNase H activity in situ detection. Issue 19 (9th September 2021) - Hu, Yalei; Xie, Qian; Chang, Li; Tao, Xueqing; Tong, Chunyi; Liu, Bin; Wang, Wei
Abstract : Radar-like monitor for RNase H detection in vitro and for intercellular imaging. Abstract : Ribonuclease H is essential for the research and development of complex pathema. The high rigidity and versatility of DNA tetrahedrons means they are often used in biosensing systems. Inspired by "radar" technology, we proposed a radar-like monitor to detect RNase H activity in vitro and in situ by integrating DNA tetrahedral elements. The structure of a radar-like monitor was self-assembled from five customized single nucleic acid strands. Four DNA strands were assembled as DNA tetrahedrons with a long strand labeled by Dabcyl (quencher) at one of the apexes, while the fifth strand (DNA–RNA heterozygous strand) was labeled with a FAM (Fluorophore) hybrid with a long strand. The fluorescence was quenched because the fluorophore and the quencher were very close. In the presence of RNase H, the RNA chain was hydrolyzed and the fluorophore released, resulting in fluorescence recovery. The radar-like monitor was used to detect the RNase H activity in vitro with a detection limit of 0.01 U mL −1 . Based on the RNase H activity detection and the inhibitory effect of natural-compounds-targeting RNase H, three inhibitors were obtained among 35 compounds extracted from Panax japonicus. Therefore, the radar-like monitor was successfully used to detect RNase H activity in situ due to the long-term anti-DNase I effect of the RNA/DNA hybrid structure and DNA tetrahedrons structure. Overall, this radar-like monitor can effectively avoid false-positive signals and significantly improve the accuracy, precision, and reliability of detection. It is expected that the development of such an intelligent nano-platform will open the door to cancer diagnosis and treatment in clinical systems.